Penyusunan Strategi Digital Marketing pada Usaha UMKM Permata Mart Kota Batam - Cuandra, Fendy; Putra, Raymond Gautama (Pakis Journal Institute, 2026)
This internship was carried out at Permata Mart, an SME engaged in the retail business of daily necessities and located in the Permata Baloi area, Batam City. The purpose of this internship was to assist Permata Mart in improving its marketing effectiveness through the implementation of digital marketing strategies. The methods used in this activity included direct observation and interviews with partners to determine the condition of the business and marketing activities that had been carried out. Based on the analysis, it was found that Permata Mart has not optimally utilized digital media as a promotional tool. Therefore, the solution provided was the development and implementation of a digital marketing strategy, such as the use of social media and registering the business location on Google Maps. The results of this internship are expected to increase business visibility, expand marketing reach, and support the competitiveness of Permata Mart.